From Brain Organoids to Networking Assembloids: Implications for Neuroendocrinology and Stress Medicine - Makrygianni, Evanthia A.; Chrousos, George P. (Frontiers in Physiology, 2021)
Brain organoids are three-dimensional tissue cultures containing multiple cell types and cytoarchitectures which may resemble fetal human brain at molecular, cellular, structural and functional levels. These organoids are being used increasingly to model brain development and disorders, however, they only partially recapitulate such processes, because of several limitations, including inability to mimic the distinct cortical layers, lack of functional neuronal circuitry, non-neural cells and gyrification, as well as because of increased cellular stress. Efforts to create improved brain organoid culture systems have led to region-specific organoids, vascularized organoids, organoids that contain glial cells, including oligodendrocytes and microglia, assembloids, sliced organoids, and polarized organoids. Assembloids, i.e., fused region-specific organoids, attempt to recapitulate inter-regional and inter-cellular interactions and neural circuitry development, because they combine multiple brain regions and/or cell lineages. As a result, they can be used to model subtle functional aberrations that reflect complex neurodevelopmental, neuropsychiatric and neurodegenerative disorders. Mammalian organisms have a highly sophisticated neuroendocrine system, the stress system, whose main task is the preservation of systemic homeostasis, when the latter is threatened by adverse forces, the stressors. The main central components of the stress system are the paraventricular nucleus of the hypothalamus, and the locus caeruleus/norepinephrine-autonomic nervous system nuclei in the brainstem; these centers innervate each other and interact reciprocally as well as with various other CNS structures. Chronic dysregulation of the stress system has been implicated in major pathologies, the so-called chronic non-communicable diseases, including neuropsychiatric, neurodegenerative, cardiometabolic, and autoimmune disorders, leading to significant population morbidity and mortality. We speculate that brain organoids and/or assembloids could be used to model the development, regulation and dysregulation of the stress system and to better understand stress-related disorders. Novel brain organoid technologies, combined with high-throughput single-cell omics and gene editing, could, thus, have a huge impact on precision medicine.